FREQUENCE OF JUXTAGLOMERULAR GRANULATED CELIS IN DEHYDRATED AND SODIUM-LOADED MICE - Al-Ani, Imad M.; Homady, Merza H. (The Iraqi Journal of Veterinary Medicine, 2022)
Fifteen albino mice were subjected to three days dehydration and fifteen albino mice were given 1% NaCl in their drinking water. Control animals were given drinking water All animals were sacrificed and kidneys were fixed in different fixatives and processed for light microscopy Section were stained for juxtaglomerular cells demonstration and the juxtaglomerular index (GI) and percentage of granulated nephron(%GN) were calculated. Kidneys from dehydrated and sodium-loaded animals showed significant decrease in both JGI and % GN and was discussed in relation to renin secretion and release.